Electric field-induced giant strain and piezoelectricity enhancement effect in (Bi1/2Na1/2)0.935+xBa0.065Ti1−x(Pr1/2Nb1/2)xO3 lead-free ceramics. Issue 3 (15th February 2016) - Wang, Chunmei; Xu, Zhijun; Cheng, Renfei; Chu, Ruiqing; Hao, Jigong; Li, Wei; Li, Huaiyong; Du, Juan; Li, Guorong
Abstract: Lead- free (Bi1/2 Na1/2 )0.935+ x Ba0.065 Ti1− x (Pr1/2 Nb1/2 ) x O3 (BNBT– x PN) piezoelectric ceramics were prepared by the conventional solid-state reaction method and the crystal structure and electrical properties were systematically investigated. X-ray diffraction patterns revealed that the (Pr1/2 Nb1/2 ) 4+ completely diffused in the BNBT lattice in the studied composition range. An appropriate amount of (Pr1/2 Nb1/2 ) 4+ additive enhanced the dielectric, ferroelectric, and piezoelectric properties of BNBT ceramics. The P r and d 33 increased from 29.1 μC/cm 2 and 121 pC/N of pure BNT to 32.8 μC /cm 2 and 221 pC/N of modified ceramics with x =0.0050, respectively. Furthermore, electric field-induced strain was enhanced to its maximum value ( S max =0.34%) with normalized strain ( d 33 * = S max / E max =567 pm/V) at an applied electric field of 60 kV/cm for x =0.0075. These findings have great potential for actuator and multifunctional device applications, which may also open up a range of new applications.